Effect of Mother Tongue on Learning Kiswahili Language in Public Secondary Schools in Kwanza Sub-County, Trans-Nzoia County, Kenya - , David Wafula Lwangale; Sarah Simiyu (IJRDO- Journal of Educational Research, 2020)
The study investigated the effect of Mother Tongue on Learning Kiswahili Language in Public Secondary Schools in Kwanza Sub-County, Trans-Nzoia County, Kenya. The study was guided by Weinreich’s (1953) theory of first language acquisition and second language learning. The theory focuses on interference defining it as those instances of deviation from the norms of either language which occur in the speech of bilingual as a result of their familiarity with more than one language. This theory has been applauded by linguists such as Gass and Selinker (2008) who assume that in the SLA, learners create a language system known as an Interlanguage. In this study, survey design was used to explore effect of interlanguage on learning of Kiswahili language in public secondary schools in Kwanza Sub-County, Trans-Nzoia County. Data collection involved administration of questionnaires, observation schedule, interview schedule and document analysis. In this research, stratified sampling was used in selecting schools. Schools sampled were: four streamed, three streamed, double streamed and single streamed. The principals and teachers of Kiswahili of sampled schools were sampled purposively. Simple random sampling technique was used in the selection of streams in multiple streamed schools. The form three students were simple randomly selected to form part of the sample. Descriptive statistics was used in analyzing data. These included percentages and frequencies. The study found out that the use of interlanguage negatively affected the learning of Kiswahili language. In addition, the study established that both teachers and students had positive attitude towards Kiswahili language. Therefore, teachers should capitalize on the positive attitude to assist students do well in Kiswahili subject. The study also found out that school language policy negatively affected performance of Kiswahili language since it was biased giving preference to English use. The study also established that students were allocated limited time to speak in Kiswahili. The use of Sheng’ negatively affects the learning of Kiswahili in secondary schools. Lastly, teachers mostly used direct method and question and answer method than any other methods of teaching Kiswahili.